The INTERNATIONAL SUSTAINABILITY UNIVERSITY EDUCATION FOR ARCHITECTURE, ENGINEERING AND CONSTRUCTION (AEC) COURSES: A CASE FOR GLOBAL CLASSROOM. - ALLU-KANGKUM, EVELYN LAMI ASHELO; Katyen, Ann Muopwun.; Chong, Jonathan David. (IJRDO - Journal of Mechanical And Civil Engineering, 2021)
Sustainability university education is targeted at social-environmental local problems to provide contextual solutions that have positive global impacts. As such, it is important for educational experiences of university students to be ascertain to close the gap between knowledge and skills for globalized sustainability education. However, not much has been pursuit in the novelty of globalization of sustainability education, particularly in Nigeria. Yet, The Global Classroom for the globalization of sustainable education provides many opportunities for the global sustainability concerns. These opportunities include; global outlook to sustainable solutions, virtual educational technologies enhancement, established international standards and quality of students, promotes cross-cultural fluency, multiple and diverse partnerships and integration of sustainability practices into university educational experiences. A two sections questionnaire survey was conducted amongst 120 academic staff of Architecture, Engineering and Construction (AEC) professionals in a Nigerian University. The theoretical underpins were validated and the contextual challenges for a Global Classroom perceived includes; lack of constant electricity and internet, differences in time zones, language barriers, lack of virtual learning technology, lack of adequate sustainability knowledge and absent of regulations to support Global Classroom. This study concludes with deduced reflections on the necessary requirements for promoting Global Classroom as its recommendations, one of which is the promotion of institutionalized regulations to support Global Classroom.